2022
DOI: 10.1021/acs.est.2c05314
|View full text |Cite
|
Sign up to set email alerts
|

Sulfidation and Reoxidation of U(VI)-Incorporated Goethite: Implications for U Retention during Sub-Surface Redox Cycling

Abstract: Over 60 years of nuclear activity have resulted in a global legacy of contaminated land and radioactive waste. Uranium (U) is a significant component of this legacy and is present in radioactive wastes and at many contaminated sites. U-incorporated iron (oxyhydr)oxides may provide a long-term barrier to U migration in the environment. However, reductive dissolution of iron (oxyhydr)oxides can occur on reaction with aqueous sulfide (sulfidation), a common environmental species, due to the microbial reduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 76 publications
(287 reference statements)
2
1
0
Order By: Relevance
“…Although the uranium removal efficiency was about 60% in the Mg 3 (PO 4 ) 2 system when the pH values were 7.0 and 9.0, the leaching rates were about 45–55%. It resulted from the remobilization of surface-adsorbed UO 2 2+ . The high leaching rate meant the considerable surface physical adsorption of Mg 3 (PO 4 ) 2 to uranyl, being similar to the results of uranium adsorption on hydroxyapatite .…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Although the uranium removal efficiency was about 60% in the Mg 3 (PO 4 ) 2 system when the pH values were 7.0 and 9.0, the leaching rates were about 45–55%. It resulted from the remobilization of surface-adsorbed UO 2 2+ . The high leaching rate meant the considerable surface physical adsorption of Mg 3 (PO 4 ) 2 to uranyl, being similar to the results of uranium adsorption on hydroxyapatite .…”
Section: Resultssupporting
confidence: 55%
“…It resulted from the remobilization of surface-adsorbed UO 2 2+ . 37 The high leaching rate meant the considerable surface physical adsorption of Mg 3 (PO 4 ) 2 to uranyl, being similar to the results of uranium adsorption on hydroxyapatite. 38 It showed the leaching risk.…”
Section: +supporting
confidence: 65%
“…In recent years, M 4,5 -edge HERFD has matured into an essential method for determining actinide electronic structure, bonding, and speciation. ,, An increasing number of studies demonstrate that the method carries sensitivity to oxidation state, 5 f ligand field splitting, and covalency. ,,, It has also been shown that additional insights can be obtained by extending HERFD measurements to include 3 d 4 f RIXS planes, particularly in identified variations in resonant versus nonresonant XES maxima. ,, The present study reports the sensitivity of 3 d 4 f RIXS to U(IV) metal–ligand bonding at both the M 5 -edge and the M 4 -edge. It is identified that the RXES part of the RIXS planes contains fine structures that are not captured via HERFD measurements.…”
Section: Discussionmentioning
confidence: 81%
“…The development of nuclear energy is important for the sustainable energy industry. The uranium ore processing, nuclear energy generation, and spent-fuel treatment leads to uranium contamination in underground water and soil environment. , Therefore, the effective disposal of radioactive uranium-containing wastewater and the study of uranium cycling in biogeochemistry are mandatory in environmental science. , Species of two predominant oxidation states, hexavalent U­(VI) in uranyl (UO 2 2+ ) and tetravalent U­(IV) or U 4+ , of environmental uranium species have been studied extensively. Noncrystalline U­(IV) species have been detected to be markedly more labile than solvable species of uranyl because they tend to be promptly oxidized and mobilized by O 2 , persulfate and bicarbonate. , Uranyl species with high aqueous solubility and mobility have huge effects on the hydrosphere and geosphere. Under anaerobic conditions, uranyl species are rapidly reduced by organophosphates to crystalline U­(IV)-phosphate minerals, which are more difficult to oxidatively reactivate than products of microbial uranyl reduction . Biological treatments are widely used for the immobilization of uranyl in aqueous solution. , Especially, biomineralization is a process in which organisms coordinated and controlled by living organisms generate inorganic minerals, with virtue of low cost and high stability of the products.…”
Section: Introductionmentioning
confidence: 99%